Аналіз фрактальних властивостей сумарного інформаційного трафіка - Макляков, В. Д. (ХНУРЕ, 2023)
In the work the numerical investigation of the properties of the additive modeling self-similar traffic, which have varying degrees of burstability is carried out. It is shown that the value of Hurst exponent of total stream is determined by the maximum value of Hurst exponent and the variation coefficients of streams.
Keywords: самоподібний трафік; сумарні самоподібні потоки; показник Херста